IMPACTO DOS SISTEMAS DE GESTÃO DA QUALIDADE, COM BASE NO PNQ E NAS NORMAS ISO 9000, NA SATISFAÇÃO DOS CLIENTES - Moreira, Beatriz Maria Figueiredo (2007)
This work presents the results of an experience carried out under the auspices of the Regional Direction of São Paulo Metropolitan, of the Brazilian post office: Empresa Brasileira de Correios e Telégrafos. In this study, customers from nine agencies of this post office certified by the ISO 9001:2000 and from others eighteen agencies that had strategically been elected for future certification had been interviewed. These units, today, are enclosed in the Model of Excellency of this post office, a model defined by the organization, based on the Criteria of Excellency of the PNQ. The results from the research on the customer satisfaction suggest that the attributes of the quality in the certified agencies had achieved greater success, obtaining a better perception from customers in relation to the performance (productivity and efficiency). However, the index differences obtained from the evaluation of the customers was not so divergent between the two systems of management. Concluding, despite the small difference, certainly, the ISO Certification contributed for the quality of the costumer services, being a demonstration of the commitment of the company in relation to its customers retail.